2015
DOI: 10.1186/s12917-015-0466-x
|View full text |Cite
|
Sign up to set email alerts
|

International Veterinary Epilepsy Task Force recommendations for a veterinary epilepsy-specific MRI protocol

Abstract: Epilepsy is one of the most common chronic neurological diseases in veterinary practice. Magnetic resonance imaging (MRI) is regarded as an important diagnostic test to reach the diagnosis of idiopathic epilepsy. However, given that the diagnosis requires the exclusion of other differentials for seizures, the parameters for MRI examination should allow the detection of subtle lesions which may not be obvious with existing techniques. In addition, there are several differentials for idiopathic epilepsy in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 76 publications
(98 reference statements)
0
48
0
Order By: Relevance
“…Because this was a retrospective study, blood tests, urinalysis, genetic and/or familial analysis according to the IVETF consensus [6] were not fulfilled in most dogs with IdE. Furthermore, MRI in our study did not correspond to the epilepsy-specific MRI protocol suggested by IVETF [10]. Although we made efforts to follow the IVETF consensus as much as possible, we had to exclude 110 dogs with epilepsy that did not satisfy the criteria e.g., our initial cohort included many dogs that had an initial epileptic seizure onset at <6 months or >6 years and/or showed neurological deficits but were not examined by MRI or CSF analysis due to various reasons such as complications in the dogs and economic compliance of owners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because this was a retrospective study, blood tests, urinalysis, genetic and/or familial analysis according to the IVETF consensus [6] were not fulfilled in most dogs with IdE. Furthermore, MRI in our study did not correspond to the epilepsy-specific MRI protocol suggested by IVETF [10]. Although we made efforts to follow the IVETF consensus as much as possible, we had to exclude 110 dogs with epilepsy that did not satisfy the criteria e.g., our initial cohort included many dogs that had an initial epileptic seizure onset at <6 months or >6 years and/or showed neurological deficits but were not examined by MRI or CSF analysis due to various reasons such as complications in the dogs and economic compliance of owners.…”
Section: Discussionmentioning
confidence: 99%
“…Although the MRI performed in this study did not adhere to the epilepsy-specific MRI protocol suggested in the IVETF proposal for the IdE tier II confidence level [6, 10], all MRI scans included T1-weighted, T2-weighted, FLAIR, and contrast-enhanced T1-weighted images in the transverse plane. Images were obtained using a 1.5-Tesla system [Visart® 1.5 Tesla, Toshiba Medical System, Tokyo, Japan (between April 2003 and October 2009)] or 3.0-Tesla system [Signa® HDxt 3.0T, GE Healthcare, Tokyo, Japan (between October 2009 and March 2013)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral, evenly and diffusely distributed symmetrical and non‐contrast‐enhancing changes were classified as postictal. The presence of concomitant postictal changes in piriform lobes and cingulate gyri, with the same MRI signal characteristics of hippocampus, was used to support the classification of hippocampal changes as postictal . If the hippocampus was involved in the borders of an ipsilateral lesion, it was considered to be lesion‐related.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of concomitant postictal changes in piriform lobes and cingulate gyri, with the same MRI signal characteristics of hippocampus, was used to support the classification of hippocampal changes as postictal. 26,27 If the hippocampus was involved in the borders of an ipsilateral lesion, it was considered to be lesion-related. Lesions were described as focal, multifocal, or diffuse and unilateral or bilateral.…”
Section: Data Collectionmentioning
confidence: 99%